2010
DOI: 10.4269/ajtmh.2010.09-0721
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Leptospirosis in Northern Iran by Nested Polymerase Chain Reaction/Restriction Fragment Length Polymorphism and Sequencing Methods

Abstract: This study was conducted to investigate the prevalence of Leptospira species in Mazandaran Province of Iran by using nested polymerase chain reaction (PCR)/restriction fragment length polymorphism (RFLP) methods and sequencing analysis. Blood samples (n = 119) were collected from humans suspected of having leptospirosis from different parts of the province in 2007. By using an indirect immunofluorescent antibody test (IFAT), we determined that 35 (29.4%) of 119 suspected cases had leptospiral antibody titers ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…The current available whole-cell vaccines cannot provide cross-protection against infection with more than 250 different Leptospira serovars known to exist and may lead to incomplete, short-term immunity and serious side effects. Despite vaccination, the disease still exists in some parts of the country [6][7][8]. The design and construction of an efficient recombinant vaccine for leptospirosis control is very important [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The current available whole-cell vaccines cannot provide cross-protection against infection with more than 250 different Leptospira serovars known to exist and may lead to incomplete, short-term immunity and serious side effects. Despite vaccination, the disease still exists in some parts of the country [6][7][8]. The design and construction of an efficient recombinant vaccine for leptospirosis control is very important [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Golsha et al in Golestan, fever, chilling and myalgia (100%) were reported as the most common clinical symptoms of leptospirosis (Golsha et al, 2007). Fever and myalgia were the most common symptoms of leptospirosis in Zakeri et al's research (Zakeri et al, 2010). In the study of Sehgal and Katz, among the various clinical symptoms, fever and headache have been referred as the most common symptoms (Katz et al, 2011;Sehgal, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome all these limitations polymerase chain reaction (PCR) have been used, which is considered sensitive and specific for the rapid detection of Leptospira in clinical samples. Evaluation of PCR-based studies for the identification and diagnosis of leptospirosis has been reported elsewhere, in humans and animals [13,28,29,30]. It has been developed for the rapid detection of Leptospira DNA and has the potential to make a dramatic impact in diagnosing leptospirosis [25].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%